Katalis Asam Padat Berbasis Karbon Tersulfonasi Pada Proses Pembuatan Biodiesel - Muhammad Hiknul Ikhsan; Umar Kalmar Nizar (Departemen Kimia FMIPA UNP, 2020)
Biodiesel is a promising alternative energy source in the future. The method of making biodiesel is the reaction of fatty acid esterification with methanol assisted by a catalyst. The catalyst that is widely developed in the process of making biodiesel is solid acid catalyst. Especially those based on sulfonated carbon. The purpose of this article is to explain the function and role of sulfonated carbon-based solid acid catalyst in the biodiesel production process. Solid acid catalyst is synthesized by sulfonation process of calcined carbon using sulfuric acid or chlorosulphonic acid. The advantage of using a solid acid catalyst is that the catalyst can be regenerated so that it can be used in several cycles. The use of solid acid catalysts can produce biodiesel with a fairly high conversion percentage. Keywords— biodiesel, solid acid catalyst, sulfonation, sulfuric acid, chlorosulfonic acid